Encyclopedia of women and religion in North America - Keller, Rosemary Skinner; Ruether, Rosemary Radford; Cantlon, Marie (Indiana University Press, 2006)
A fundamental and well-illustrated reference collection for anyone interested in the role of women in North American religious life